Artificial diets affect glucose and lipid metabolism, antioxidant capacity, and inflammatory response in the muscle of mandarin fish (Siniperca chuatsi) - Fang, Wei; Leng, Xiangjun; Yun, Biao; Wang, Lei; Qian, Xueqiao (Frontiers in Marine Science, 2024)
Mandarin fish (Siniperca chuatsi) can adapt to artificial diets, with the improvement of domestication level. However, the effects of artificial diets on the muscle health of fish are unclear. In this study, 480 homogenous-sized mandarin fish (initial weight of 25.1 ± 0.1 g) were randomly divided into two groups and fed with artificial diets or live prey fish for eight weeks. The transcriptome sequencing analysis identified that artificial diets primarily affected glucose metabolism, lipid metabolism, and immune system in the muscle. Furthermore, artificial diets induced excessive glycogen accumulation in the muscle by increasing the mRNA expression of gluconeogenesis-related genes and decreasing the mRNA expression of glycolysis-related genes. Meanwhile, artificial diets significantly increased triglyceride accumulation in the muscle by upregulating the activity of fatty acid synthetase and the mRNA expression of lipid synthesis-related genes, including srebp1, fas, and plin2. Artificial diets significantly increased the level of malondialdehyde, leading to oxidative stress in the muscle. Besides, artificial diets also upregulated the mRNA expression of pro-inflammation cytokines, including il-1β, ifn-γ, and tnfα. In conclusion, artificial diets disrupted glucose and lipid metabolism and induced oxidative stress and inflammation in the muscle of mandarin fish.